Can agroforestry option values improve the functioning of drivers of agricultural intensification in Africa? - Carsan, S.; Stroebel A; Dawson, I.; Kindt, Roeland; Mowo JG; Jamnadass, Ramni H. (Elsevier, 2014)
Agricultural commodity production in a changing climate scenario is undergoing sustainability challenges due to degradation of soil fertility, water and biodiversity resources. In Africa, yields for important cereals (e.g., maize) have stagnated at 1 t ha−1 due to land degradation, low fertilizer use and water stress. Resource-conserving options such as agroforestry promote integrated management systems that relate livelihoods and ecosystem service functions to agricultural production. Low input practices including improved fallows using legumes in rotations or intercrops can restore soil nutrients, improve soil carbon and reduce reliance on fertilizer use by 50%. We review how agroforestry can sustain agricultural intensification in Africa by regulating ecosystem functions such as nutrient recycling, water use, species diversity and agrochemical pollution.